Experiences of women with disabilities during and after COVID-19: Needs, sources of support and implications for policy and practice - Adi Finkelstein; Sara Genut; Anat Golos (PLoS ONE, 2026)
Approximately 700 million women and girls worldwide live with disabilities, facing compounded discrimination due to both gender and disability. Despite their large numbers, they are often excluded from decision-making and rendered invisible. Research shows that crisis such as nature disasters and public health crises affects people with disabilities more severely than the general population, and women more than men. Yet, studies focusing specifically on women with disabilities in such contexts remain scarce. The present qualitative study aimed to address this gap by analyzing 56 semi-structured interviews with women with motor and/or sensory impairments about their life experiences during COVID-19 and afterwards, using reflexive thematic analysis. Participants aged 26–69, mostly with motor impairments (66.1%), reported satisfaction with their health (71.4%). Findings are organized into four main themes and six sub-themes corresponding to the components of the International Classification of Functioning, Disability, and Health (ICF) as follows: Physical and mental health through daily care and environmental contexts; Navigating accessibility and attitudinal barriers in daily life; Maintaining decision-making autonomy and financial independence; Family and social relationships as sources of support. The findings demonstrate multifaceted impacts on women with disabilities across personal, social, and contextual domains, during both stable periods and crises. To effectively address their needs, policymakers should incorporate the perspectives of women with disabilities in the planning of support programs for both routine periods and crises responses.